2021
DOI: 10.1002/deo2.38
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound‐guided fine‐needle biopsy for the diagnosis of gastric linitis plastica

Abstract: We report two cases of patients with gastric linitis plastica (GLP), in which the histopathological diagnosis was made by endoscopic ultrasound‐guided fine‐needle biopsy (EUS‐FNB) using a Franseen‐tip needle. Esophagogastroduodenoscopy findings showed mucosal swelling and poor distensibility of the gastric antrum. Abdominal computed tomography findings showed significant thickening of the gastric wall at the antrum. Conventional endoscopic and bite‐on‐bite biopsy were attempted but resulted in failure to diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Adequate specimens to evaluate malignancy are difficult to obtain from submucosa lesions, including GLP. As deep endoscopic biopsy techniques, endoscopic mucosal resection (EMR), bite-on-bite techniques, mucosal incision-assisted biopsies, and EUS-FNBs are used[ 13 ]. Although the European Society of Gastrointestinal Endoscopy recommends a MIAB or EUS-FNB for the tissue diagnosis of subepithelial lesions, including gastrointestinal stromal tumor (GIST)[ 14 ], there is no standard method for making a tissue diagnosis of GLP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate specimens to evaluate malignancy are difficult to obtain from submucosa lesions, including GLP. As deep endoscopic biopsy techniques, endoscopic mucosal resection (EMR), bite-on-bite techniques, mucosal incision-assisted biopsies, and EUS-FNBs are used[ 13 ]. Although the European Society of Gastrointestinal Endoscopy recommends a MIAB or EUS-FNB for the tissue diagnosis of subepithelial lesions, including gastrointestinal stromal tumor (GIST)[ 14 ], there is no standard method for making a tissue diagnosis of GLP.…”
Section: Discussionmentioning
confidence: 99%
“…Although the European Society of Gastrointestinal Endoscopy recommends a MIAB or EUS-FNB for the tissue diagnosis of subepithelial lesions, including gastrointestinal stromal tumor (GIST)[ 14 ], there is no standard method for making a tissue diagnosis of GLP. In the previous articles, an EUS-FNB for GLP cases with a negative endoscopic biopsy was reported to be useful in that EUS could directly visualize whether or not the target had been punctured properly, and the positive rates were high with few adverse events (Table 2 )[ 13 , 15 - 17 ]. However, Zhou et al [ 18 ] conversely reported that the diagnostic yield of EMR with the bite-on-bite technique for gastric-infiltrating tumors, including GLP, was 82.2% (23/28).…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi et al reported two patients with GLP, in which EUS-FNB with a Franseen needle was used to successfully perform immunological staining and confirm diagnosis after a failed conventional endoscopic biopsy. 8 Currently, 19-gauge, 22gauge, and 25-gauge Franseen needles are available. In general, finer needles are more flexible and easier for puncturing; whereas, they tend to obtain a smaller sample.…”
Section: Discussionmentioning
confidence: 99%